Quality Analysis of Discovery Learning-Based Learning Devices for Human Digestion - Hidayatulloh, Hendik; Andayani, Dewi; Artika, Wiwit; Rahmatan, Hafnati; Safrida (Jurnal Pendidikan Sosiologi dan Humaniora, 2026)
The Merdeka Curriculum emphasizes innovation, flexibility, and students’ ability to adapt to the demands of the 21st century. To support its implementation, teachers are required to develop high-quality learning tools that facilitate active and meaningful learning. This study aimed to evaluate the quality of Discovery Learning-based learning tools integrated with virtual laboratory media on the topic of the human digestive system and to investigate teachers’ perceptions of the developed learning tools. A quantitative approach with a descriptive research design was employed. The research subjects consisted of two education and media experts, three biology teachers at SMA Negeri 2 Banda Aceh, and 30 twelfth-grade students who had previously studied the human digestive system. The developed learning tools included teaching modules, Student Worksheets (LKPD), and virtual laboratory media. The learning tools were evaluated using Gregory’s validity test and interrater reliability with Cohen’s Kappa, while the test instruments were analyzed using Aiken’s V, Product Moment validity, Cronbach’s Alpha reliability, difficulty level, and discrimination index. Teachers’ perceptions were analyzed using the average percentage method. The results indicated that all Discovery Learning-based learning tools achieved a “very valid” category, while teachers’ perceptions were categorized as “very good.” These findings demonstrate that the developed learning tools meet the required standards of validity and practicality, making them appropriate for supporting biology learning on the human digestive system topic under the Merdeka Curriculum.